Inhibition Mechanism of Pleurotus citrinipileatus Sing. Ergothioneine on Pancreatic Lipase Activity - Zhangchen XIA; Xiaohui MENG; Ru FANG; Yanqing MAO; Junwen CHENG; Yanbin WANG; Juan XU; Liang HE (Shipin gongye ke-ji)
The interaction between Pleurotus citrinipileatus Sing. ergothioneine (PCEGT) and pancreatic lipase (PL) was studied by analyzing multiple spectroscopies including enzyme kinetics, ultraviolet absorption (UV), fluorescence spectroscopy, synchronous fluorescence spectroscopy and 3D fluorescence spectroscopy as well as the PCEGR-PL interaction mechanism by molecular docking in order to clarify its inhibitory mechanism. The results showed that the inhibition process of PCEGT on PL was reversible non-competitive with 15.29 mg/mL of the half-maximal inhibitory concentration (IC50). The UV spectrum indicated there was a π→π* transition produced by the peptide bond C=O group of PL as the mass concentration of PCEGT increased, which could reflect the reinforcement of polarity and hydrophilicity. Fluorescence spectra data revealed PCEGT could efficiently static-quench the intrinsic fluorescence of PL by changing its space structure. Based on the Lineweaver-Burk equation, the binding constants (Ka) under three different temperatures were obtained. Among them the Ka value was estimated to be 1.55×103 L/mol with approximately 1 binding site at 298 K. The thermodynamic parameters including enthalpy change and enthopy change calculated by Van't Hoff's law were to be −8.57 kJ/mol and 2.55 J/(mol·K), respectively. PCEGT might combine with the amino acid residues of PL via hydrogen bonding and electrostatic force. With the increase of the concentration of PCEGT, synchronous fluorescence intensity and 3D fluorescence spectra demonstrated that the failing hydrophobicity and incremental polarity of PL could be achieved evidencing by obvious redshifts of maximum absorption peaks (6 and 3 nm) and descent fluorescence intensities (32.2% and 25.6%). Molecular docking results further reinforced that PCEGT interacted with amino acids outside catalytic site of PL via hydrogen bonding, charge attraction and van der waals' force, resulting in the inhibition of PL. This study was beneficial for the deep understanding the hyperlipidemia of PCEGT from molecular mechanism and boosted the future health food processing of Pleurotus citrinipileatus Sing..